Russian energy supplies to Europe: The Crimea crisis. Mutual dependency, lasting collateral damage and strategic alternatives for the European Union - Kirsten Westphal (Stiftung Wissenschaft und Politik (SWP), 2014)
At least in the medium term Russia will remain the backbone of Europe's energy supply. While the European Union possesses enough storage capacity to bridge a temporary interruption of gas supplies routed through Ukraine, it has precious few other immediate alternatives. In the medium to long term, however, Europe has diversification options that would also expand its foreign policy leeway. Overall, strong reciprocal dependencies and economic rationality should mitigate against allowing the political conflict to spread into economic and energy relations. Otherwise both sides will suffer massive economic harm. (SWP Comments)
Keywords: 320